2016
DOI: 10.1161/strokeaha.116.013105
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Histology Suggests Cardioembolic Cause in Cryptogenic Stroke

Abstract: The study was approved by the Institutional Review Board, and informed consent of patients was obtained. A total of 145 intracranial Background and Purpose-Ischemic stroke of undetermined cause is a major health issue because of its high frequency and clinical relevance. Histopathologic analysis of human thrombi, retrieved from stroke patients with large-vessel occlusion during mechanical thrombectomy, may provide information about underlying pathologies. This study examines the relationship between stroke cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
221
3
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(253 citation statements)
references
References 36 publications
23
221
3
6
Order By: Relevance
“…As reported by Boeckh-Behrens et al, 10 we also found a strong association of cryptogenic strokes with cardioembolic strokes compared with noncardioembolic strokes, which further strengthens the theory that strokes where the pathogenesis after complete diagnostic workup is classified as cryptogenic are mostly of cardiac origin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As reported by Boeckh-Behrens et al, 10 we also found a strong association of cryptogenic strokes with cardioembolic strokes compared with noncardioembolic strokes, which further strengthens the theory that strokes where the pathogenesis after complete diagnostic workup is classified as cryptogenic are mostly of cardiac origin.…”
Section: Discussionsupporting
confidence: 91%
“…This supports recent studies by Boeckh-Behrens et al, 8,10 Niesten et al, 13 and Simons et al, 7 that report about an association of high fibrin and low RBC proportion in cardioembolic thrombi and which are contrary to the concept of red and erythrocyte-rich cardioembolic thrombi (Figure 1). The contradictory findings of Kim et al 14 may be related to differences in methods and study population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Small foci of myocardial injury that generate cerebral emboli is an intriguing mechanism raised by this work. Consistent with this is the recent finding that emboli extracted from the brains of individuals with ESUS during acute stroke treatment show features consistent with cardiogenic emboli 7. AF is associated with elevated troponin and subclinical AF has been suggested as the cause underlying cryptogenic stroke 8, 9.…”
supporting
confidence: 66%
“…Mechanical thrombectomy is notable because it allows for histologic evaluation of clots retrieved from human intracranial arteries, potentially broadening our insight into stroke etiology as well as our understanding of clot appearance on imaging studies. Several recent studies involving the histologic analysis of intracranial clots retrieved by mechanical thrombectomy in acute stroke patients have focused on blood cell composition in clots using either hematoxylin and eosin or immunohistochemical staining 2, 3, 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%